Labor market flexibility and unemployment in Chile and Uruguay - Allen, Steven; Cassoni, Adriana; Labadie, Gastón (Estudios de Economía, 2016)
This study compares evidence on wage rigidity in Chile and Uruguay to determine whether differences in labor market flexibility could have had an impact on the very different patterns of unemployment observed in the two countries. Phillips curve estimates show that wages in Uruguay were highly flexible at the aggregate level during the period when the military government was in power, but became more rigid with the return of democracy and collective bargaining. Rising minimum wages and indexation arrangements are plausible explanations of some of the high unemployment in Chile in the late 1970s and early 1980s. At the micro level, we find much more relative wage adjustment across industries in Chile than Uruguay and that labor in Chile is drawn toward sectors with rising relative wages.